2023
DOI: 10.59698/vilvatikta.v1i1.5
|View full text |Cite
|
Sign up to set email alerts
|

Kontribusi Mata Pelajaran Muatan Lokal Bahasa Jawa Dalam Penerapan Kurikulum Merdeka

Abstract: Penelitian ini bertujuan untuk mendeskripsikan kontribusi pelajaran muatan lokal bahasa Jawa dalam penerapan kurikulum merdeka. Penelitian ini menggunakan metode kualitatif deskriptif. Pengumpulan data dilakukan dengan Teknik wawancara, observasi, dan dokumentasi. Data yang terkumpul dilakukan analisis dengan Teknik Miles dan Huberman: penggolongan data, reduksi data, penyajian data, dan penarikan kesimpulan. Validitas data dilakukan dengan triangulasi data dan sumber. Informan pada penlitian ini meliputi guru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
1
0
1
Order By: Relevance
“…As a result, teachers use various methods in teaching local content in regional languages to attract students' attention while learning. A study by Verrysaputro &;Subekti, (2023) shows that learning using various learning methods can help students convey their ideas, thoughts, and views. Moreover Yektiningtyas &; Modouw, (2017) also, in their research, revealed that the right language teaching method in the application of Sentani cultural elements will increase the enthusiasm for learning of the students.…”
Section: Process Evaluationmentioning
confidence: 99%
“…As a result, teachers use various methods in teaching local content in regional languages to attract students' attention while learning. A study by Verrysaputro &;Subekti, (2023) shows that learning using various learning methods can help students convey their ideas, thoughts, and views. Moreover Yektiningtyas &; Modouw, (2017) also, in their research, revealed that the right language teaching method in the application of Sentani cultural elements will increase the enthusiasm for learning of the students.…”
Section: Process Evaluationmentioning
confidence: 99%
“…Bahasa Jawa merupakan salah satu pelajaran yang terdapat di SD sebagai pelajaran muatan lokal (Verrysaputro & Subekti. 2023).…”
unclassified